MENINGKATKAN KETERAMPILAN TATA BUSANA MEMBUAT POLA ROK MELALUI SELF REGULATED LEARNING BAGI ANAK TUNARUNGU - Hasneli, Fatma; Z, Martias (Inspiratif Pendidikan, 2021)
The research was conducted based on problems that found in class IX of  SLB Negeri 1 Ranah Pesisir, and the students GA and GE as background who felt troble about making the A Line skirt pattern . The research purposes of this action are to: 1. Determine the process of improving dressmaking skills in making skirt patterns for deaf children in class IX at SLB Negeri 1 Ranah Pesisir . 2. Improve teacher skills in developing and varying learning methods . 3. Make students to be able to make skirt patterns. This study uses self-regulated learning with a type of classroom action research conducted form of collaboration with friends. The research subjects were class IX deaf children. In this study the data obtained through observation and practical research were analyzed qualitative and quantitative. The research activity was carried out in two cycles, each cycle consisting of two meetings. The activity begins with planning, implementing of the actions, observing and reflecting. The results of the research before being given the action showed the initial ability of deaf children to make dress patterns in skirt patterns, GA got a value of 37.14%, while GE got 32.85%. In the first cycle there was an increase, GA got a value of 81.43% and GE got a value of 81.43%. In the end of second cycle, the students value be drastically increased GA scored 100% and GE also scored 100%. Based on the increase in the value in each cycle, it can be concluded that the application of self-regulated learning in children's learning of dressmaking skills can improve student’s abilities in making skirt patterns for deaf children class IX at SLB Negeri 1 Ranah Pesisir.